(3QSGdI aj GdMOhOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO aEf CUObGFi SCdhfi ai Cf Cedi Ydjge MOhO CTjA jWGdHhfi HJMOjOgG aGSJYLHJ ef Pdc YdekG HGfg cGdCeQ GdeJYOO Ydi GdHTQ ShGA cGf JMOjOkG Gh QSekG s
(3BNQgG (B:s
(3hGeG HGdEJUGd cCYVGA GdMjhGf hCMb gPG GdHGH HGSe GdEJMGO gh MUhd LSe hGMO HGdYOO ef ELJeGY CLSGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B861s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs